Delta waters : research to support integrated water and environmental management in the lower Mississippi River (National Academies Press, 2013)
"The Water Institute of the Gulf is a not-for-profit, independent research institute dedicated to advancing the understanding of coastal, deltaic, river and water resource systems, both within the Gulf Coast and around the world. Their mission supports the practical application of innovative science and engineering, providing solutions that benefit society. Those who make policy for coastal and deltaic systems, as well as managers of natural resources, need high-quality science and engineering to guide their decisions. The Water Institute of the Gulf began operations in 2012 to address exactly this sort of challenge. Delta Waters offers advice to The Water Institute of the Gulf that it might use as part of its strategic planning process. This report focuses on strategic research to support integrated water resources management in the lower Mississippi River delta and includes international comparative assessments. The recommendations of Delta Waters promote a human and environmental systems approach to scientific research that supports integrated water and environmental resources management in the lower Mississippi River and delta, and offers ideas regarding comparative assessments with other, relevant deltaic regions around the world. This report provides input for research into common deltaic problems and challenges, identifies strategic research for The Water Institute of the Gulf, and suggests ways that the organization can utilize knowledge gained from the lower Mississippi River and delta system in developing a research program to support water management decisions in other large river/delta complexes."--Publisher's description.